Evaluation of Antibacterial Activities for Poly-Dl-Lactic Acid Nanosheet on the Biomimetic Sharkskin - Shunsuke, Nakano; Alyssa Asong, Ananthan; Mohd Danial, Ibrahim; Dayang Salyani, Abang Mahmod; Awang Ahmad Sallehin, Awang Husaini; Ngieng, Ngui Sing; Yuta, Sunami (2023)
The purpose of this study is to quantitatively examine whether antimicrobial activity varies with the thickness of the PDLLA nanosheets when placed on a PDMS surface with or without biomimetic shark skin surfaces. Sharks are known to have an antifouling property due to the rivulet structure of grooves spaced tens of μm apart covering their skin. The riblet structure reduces the area to which organisms adhere and prevents contact with small dirt and bacteria. In this study, a PDMS elastomer-embedded stamping method consisting of polydimethy lsiloxane PDMS was used to achieve the biomimicry of sharkskin. The surface morphology before and after the nanosheet was applied was then observed with a scanning electron microscope to create a bacterial mass reference line to evaluate its antimicrobial activity. As a result, a decrease in antimicrobial activity was observed in the biological model compared to the flat surface. In addition, a small decreasing trend in antimicrobial effect was seen when the film thickness exceeded 100 nm in nanosheets with different film thicknesses, indicating that the antimicrobial activity on the surface increased as the film thickness became thicker and less able to follow the surface irregularities.